THE COMPARISON RESEARCH ON DESIGN METHODOLOGY OF PINS - ZHANG Tao; WANG NingChang; CHENG Xin; JIANG Feng (Jixie qiangdu)
Geometry design of pin is usually performed on static shear strength criterion,ignoring the pin bending deformation and stress concentration of lubrication hole. The pin which is designed by static shear strength criterion appears premature failure. The design methods considering static shear,bending deformation and stress concentration proposed in this paper. Through the comparison among three design methods,it finds that the diameter designed with different method are different,which is associated with load and yield strength; The maximum contact stress of three stress distribution models have been analyzed,it finds that the contact stress calculated with different stress distribution models are different,which is related to load. The maximum contact stress increases with the increase of fit clearance.